1979
DOI: 10.1042/bj1780681
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of phosphatidylinositol turnover in stimulus–secretion coupling. Studies with rat peritoneal mast cells

Abstract: Histamine secretion and phosphatidylinositol turnover were compared in antigen-sensitized rat peritoneal mast cells stimulated with a number of different ligands. A small and variable increase in the incorporation of [(32)P]P(i) and of [(3)H]inositol into phosphatidylinositol was observed when the cells were treated with immunoglobulin E-directed ligands (antigens and concanavalin A), and this was accompanied by a low amount of secretion (<10% of total cell histamine). In the presence of added phosphatidylseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Second, there is an obligate role for DAG generation during exocytosis in neurons to facilitate activation of Munc13 (Brose and Rosenmund, 2002). Third, activation of exocytosis stimulates PLC in a number of cell types, including adrenal chromaffin cells (Whitaker, 1985) and RPMCs (Cockcroft and Gomperts, 1979). Finally, U73-122 and isoform-specific PLC antibodies were found to inhibit chromaffin-cell exocytosis (O'Connell et al, 2003).…”
Section: A General Role For Plc In Exocytosis?mentioning
confidence: 99%
“…Second, there is an obligate role for DAG generation during exocytosis in neurons to facilitate activation of Munc13 (Brose and Rosenmund, 2002). Third, activation of exocytosis stimulates PLC in a number of cell types, including adrenal chromaffin cells (Whitaker, 1985) and RPMCs (Cockcroft and Gomperts, 1979). Finally, U73-122 and isoform-specific PLC antibodies were found to inhibit chromaffin-cell exocytosis (O'Connell et al, 2003).…”
Section: A General Role For Plc In Exocytosis?mentioning
confidence: 99%
“…The activation involves an increase in the rate of turnover of the phosphatidylinositol cycle (Cockcroft & Gomperts, 1979a) which probably precedes and may regulate a subsequent flux of Ca2+ into the cytosol (Foreman, Hallett & Mongar, 1977). This triggers the exocytotic process which leads to the release of histamine (Gomperts, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…It is unresolved whether the phos pholipids facilitate the interaction of the ionophore with the cell membrane or whether they supply the cells with an addi tional source of arachidonic acid which is then liberated in the course of cell activa tion. It has also been reported that phospha-tidylinositol enhances the ionophore-and antigen-induced histamine release (9).…”
Section: Discussionmentioning
confidence: 99%